Muscle‐tendon morphology and function following long‐term exposure to repeated and strenuous mechanical loading. (19th April 2020) - Bissas, Athanassios; Havenetidis, Konstantinos; Walker, Josh; Hanley, Brian; Nicholson, Gareth; Metaxas, Thomas; Christoulas, Kosmas; Cronin, Neil J.
Abstract : We mapped structural and functional characteristics of muscle‐tendon units in a population exposed to very long‐term routine overloading. Twenty‐eight military academy cadets (age = 21.00 ± 1.1 years; height = 176.1 ± 4.8 cm; mass = 73.8 ± 7.0 kg) exposed for over 24 months to repetitive overloading were profiled via ultrasonography with a senior subgroup of them (n = 11; age = 21.4 ± 1.0 years; height = 176.5 ± 4.8 cm; mass = 71.4 ± 6.6 kg) also tested while walking and marching on a treadmill. A group of eleven ethnicity‐ and age‐matched civilians (age = 21.6 ± 0.7 years; height = 176.8 ± 4.3 cm; mass = 74.6 ± 5.6 kg) was also profiled and tested. Cadets and civilians exhibited similar morphology (muscle and tendon thickness and cross‐sectional area, pennation angle, fascicle length) in 26 out of 29 sites including the Achilles tendon. However, patellar tendon thickness along the entire tendon was greater ( P  < .05) by a mean of 16% for the senior cadets compared with civilians. Dynamically, cadets showed significantly smaller ranges of fascicle length change and lower shortening velocity in medial gastrocnemius during walking (44.0% and 47.6%, P  < .05‐.01) and marching (27.5% and 34.3%, P  < .05‐.01) than civilians. Furthermore, cadets showed lower normalized soleus electrical activity during walking (22.7%, P  < .05) and marching (27.0%, P  < .05). Therefore, 24‐36 months of continuous overloading, primarily occurring under aerobic conditions, leads to more efficient neural and mechanical behavior in the triceps surae complex, without any major macroscopic alterations in key anatomical structures.